The Effectiveness of Integrating Augmented Reality in Education: A Review of the Literature from 2019 to 2022 - El-GHERYB, Chaymae (Journal of Educational and Psychological Sciences, 2023)
Augmented reality technology is one of the most prominent modern technologies in education that integrates the real environment of the user along with digital education objects in order to support the educational stance in an intriguing way that helps facilitate the understanding of abstract concepts. This technique represents a significant paradigm shift to integrate modern technologies into the educational process through which to design and build virtual learning environments similar to the realistic environment of learners. Moreover, these virtual environments can contribute to learners’ acquisition of highly, necessary executional skills. Thereby reducing the margin of error in real practice. This study aims to present a theoretical framework, identify a cluster of concepts linked to the integration of augmented reality in the field of education. It also attempts to demonstrate augmented reality’s added value and advantages by addressing and investigating the issue of the effectiveness of integrating augmented reality into the educational process. In this regard, the study reviews the already existing literature related to this subject between 2019 and 2022 through a survey of a series of previous studies and an exploration of a set of databases. Finally, The study concludes that the integration of augmented reality techniques in education is effective for several purposes as it increases the learner’s motivation and commitment, enhances his/her attention and awareness processes and also contributes to the development of creative thinking skills and educational achievement.